Optimising the wave attenuation of bamboo fences using the numerical wave model SWASH - Alferink, Marijn; Gijon Mancheno, Alejandra; Suzuki, Tomohiro; Reniers, Ad (Journal of Coastal and Hydraulic Structures, 2023)
Mangroves protect tropical coastlines from flooding and erosion, reducing flood risks along coastal communities worldwide. Nevertheless, mangrove forests have experienced considerable losses due to activities like urbanization and aquaculture, exposing coastal areas to wave attack. To restore mangroves at eroding coastlines, structures formed by bamboo poles and a brushwood filling are used to shelter the coast from waves, and create a favourable habitat for mangrove colonization. However, these structures often lose their brushwood filling during storms, resulting in high maintenance costs. This study proposes a new type of design to reduce maintenance expenses, consisting of only vertical bamboo poles without a filling of brushwood. Structure designs are evaluated for a case study in Demak, Indonesia, using the numerical wave model SWASH to predict wave attenuation through the structures. Field measurements and WaveWatch III data are analyzed to obtain the design conditions for the structures in Demak. SWASH is validated against laboratory experiments, and applied to investigate the optimum number of rows and their optimum spacing (in the direction of wave propagation). The model shows that for a structure consisting of two rows of bamboo poles, the transmission rate Et/Ei decreases from 75% to 55% when the row spacing in the wave direction is increased from sx = 0.42 m to sx = 5.8 m. Larger spacings do not result in less transmission, and at least three rows are needed to have a transmission rate lower than 50 % - a common wave reduction target used in restoration efforts with structures. This study thus identifies potential strategies to maximize wave attenuation by bamboo structures, which can be used to reduce wave attack along muddy coasts without the need of a brushwood filling. Hereby, it provides an economically and user friendly alternative with respect to the previous brushwood structure designs, as it requires less material costs and maintenance. In addition, this study presents a new method to schematize these kind of structures in SWASH in an efficient way.